A construção da Usina Hidrelétrica Itá no município de Aratiba-RS: análise da transformação do lugar e da paisagem a partir das narrativas de moradores e professores - Carniel, Alexandra (2021)
The place and the landscape are essential geographic concepts in the problematization of the situation where we live and in the understanding of the world. The following research addresses the transformations of the place and landscape in the municipality of Aratiba, Rio Grande do Sul from the construction of the Itá Hydroelectric Power Plant. Its objective is to elaborate, through the narratives of residents and teachers of the municipality, didactic-pedagogical material that can contribute to the representation of the historical transformations of the local landscape. The research methodology is a case study, characterizing the research as qualitative by conducting narrative interviews with residents and teachers in the municipality of Aratiba who experienced the process of installation, construction and operation of the HPP – Itá. Thirty narrative interviews, twenty interviews with residents of affected areas and ten interviews with teachers of the municipality were carried out. Through interviews with residents, it was possible to perceive emotion in their speeches, the recollections and the relationship of affection, belonging and nostalgia for old places and landscapes. The teachers' narratives made it possible to reflect on the various impacts of the HPP and its relations with the teaching of Geography, emphasizing the importance of understanding the local landscape to understand the history of the place. From interviews with residents and teachers via content analysis, a didactic sequence was created, based on the transformation of the local landscape and the new features of places in Aratiba, with activities that seek to combine the teaching of Geography with Environmental Education. As a result of the study, we verified the great demographic impact of the HPP for the municipality of Aratiba with a decrease in the number of inhabitants; the emptying of rural areas; the closing of rural schools; cultural losses in communities; as well as positive balances, such as ICMS (Tax On the Movement of Goods and Services) collection; greater investments by the government in health, education and infrastructure. We conclude that, despite the initial intent, there is great difficulty in implementing tourism as an economic activity that overcomes the changes caused in the city and we ratify the importance of studies on hydroelectric plants aimed at teaching Geography and the production of teaching materials that point out the changes and the power relations that are expressed in the territory with the installation of hydroelectric projects.